2013
DOI: 10.1200/jco.2012.46.6441
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Selection Design Trial Evaluating CD8+-Enriched Versus Unselected Tumor-Infiltrating Lymphocytes for Adoptive Cell Therapy for Patients With Melanoma

Abstract: A B S T R A C T PurposeAdoptive cell therapy (ACT) with autologous tumor-infiltrating lymphocytes (TILs) and high-dose interleukin-2 (IL-2) administered to lymphodepleted patients with melanoma can cause durable tumor regressions. The optimal TIL product for ACT is unknown. Patients and MethodsPatients with metastatic melanoma were prospectively assigned to receive unselected young TILs versus CD8 ϩ -enriched TILs. All patients received lymphodepleting chemotherapy and high-dose IL-2 therapy and were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(144 citation statements)
references
References 29 publications
2
140
1
1
Order By: Relevance
“…2,3,6,10 This immune reaction is believed to be beneficial, leading to the overall improved survival in these patients, 2,3,6,10 such as seen in some other lymphoid-rich neoplasms of both thymic 2 and nonthymic origin. [11][12][13][14][15] It is not clear what mechanism initially triggers such immune reaction, or why this type of reaction only occurs in a subset of thymic epithelial neoplasms. In addition, it is not certain whether the mechanism is a localized or more of a systemic process.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,6,10 This immune reaction is believed to be beneficial, leading to the overall improved survival in these patients, 2,3,6,10 such as seen in some other lymphoid-rich neoplasms of both thymic 2 and nonthymic origin. [11][12][13][14][15] It is not clear what mechanism initially triggers such immune reaction, or why this type of reaction only occurs in a subset of thymic epithelial neoplasms. In addition, it is not certain whether the mechanism is a localized or more of a systemic process.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] Adoptive transfer of ex vivo-derived EBV-specific CTLs to reconstitute EBV-specific T-cell immunity 3,26 is a logical approach for patients in whom PTLD develops. This disease represents an ideal target for adoptive T-cell therapy because of the high level expression of immunogenic antigens from EBV presented by excellent antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the particular case of TIL therapy, persistence of transferred tumor-specific T cell clones is associated with tumor regression (8). Moreover, retrospective clinical studies have shown an association of autologous tumor recognition by TILs and clinical response (9,10), which suggests that enrichment of tumor-reactive cells could enhance clinical efficacy. However, the identification of the diverse repertoire of tumor-reactive cells limits the ability to study these cells, enhance clinical efficacy, and extend this therapy to other malignancies.…”
Section: Introductionmentioning
confidence: 99%